(untitled) (Nigerian Journal of Physiological Sciences, 2021)
The neuroprotective effects of the aqueous extract of Daucus carota (Dc) tuber against arsenic-induced oxidative damage on the developing cerebellum of Wistar rats were studied. Twenty-five pregnant rats (110-200g) were divided into five groups (n=5) – control received distilled water; Arsenic (As); Dc (200mg/kg); Dc (200mg/kg) +As; Vitamin C (Vc) (100mg/kg) +As. The pregnant rats in all the groups were treated orally from the first day of pregnancy to postnatal day 21. The Dc extract and Vc were administered one hour before the administration of As. Body weight of the pups on days 1, 7, 14, 21 and 28 were recorded, while neurobehavioural (forelimb grip strength and negative geotaxis) tests were done on day 21 pups. The rats were sacrificed and cerebellar tissues were collected for oxidative stress, histological (H and E), and immunohistochemical studies. Decreased forelimb grip strength, increased lipid peroxidation and decreased glutathione, glutathione peroxidase, catalase and superoxide dismutase was observed in the As group compared with the control and other treated groups. Histologically, the cerebellar cortex of the As pups showed persistent external granular layer (EGL) on postnatal day 21, reduced thickness of the molecular layer (ML) on postnatal day 28, pyknotic and depleted Purkinje cells compared with the control and other treated rats. Immunohistochemical evaluations of the cerebellar cortex showed astroliosis in the As-treated group on day 21 pups compared with the control and other treated groups. Aqueous extracts of Daucus carota and Vitamin C reversed the toxicity caused by arsenic. From the results of the study, arsenic-induced oxidative stress with morphological alterations in the perinatal developing rat cerebellum. Extracts of Daucus carota exhibited antioxidant activity as such may be a potential neuroprotective agent.